The Redefining “Luck’’ As Ego - Defense Mechanism Of Main Character In Luck (2022) Movie - Sari, Amanda Novera; Rahayu, Masnia (Faculty of Social and Political Sciences University of Bangka Belitung, 2024)
Freud's psychoanalysis provides useful insights into how characters deal with internal conflict and emotional distress together. This study explores the animated film Luck (2022) through the perspective of Freud's psychoanalytic theory, with a particular emphasis on the psychological ego defense mechanisms. Freud's structural model of the human mind, which includes the id, ego, and superego, offers a framework for comprehending the character's ongoing misfortune. Sam, the protagonist, struggles with her insecurities and emotional problems, and her misfortune represents internal psychological conflicts. Sam's defense mechanisms, which include projection, displacement, and rationalization, protect her from emotional pain while fueling her desire for luck. The id fuels her desire to protect her friend Hazel from loneliness, whereas the ego helps her cope with failures through displacement and rationalization. The superego eventually leads her to self-acceptance and emotional maturity. The analysis redefines luck in the film as a metaphor for Sam's psychological journey, showing how she progresses from unconscious instinct to moral clarity, ultimately portraying luck as an expression of personal resilience and self-discovery.